2017
DOI: 10.1038/s41598-017-12343-1
|View full text |Cite
|
Sign up to set email alerts
|

A distributional multivariate approach for assessing performance of climate-hydrology models

Abstract: One of the ultimate goals of climate studies is to provide projections of future scenarios: for this purpose, sophisticated models are conceived, involving lots of parameters calibrated via observed data. The outputs of such models are used to investigate the impacts on related phenomena such as floods, droughts, etc. To evaluate the performance of such models, statistics like moments/quantiles are used, and comparisons with historical data are carried out. However, this may not be enough: correct estimates of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 38 publications
0
25
0
Order By: Relevance
“…The time-varying moment model that expresses the distribution parameters or moments as functions of time or some other explanatory variable or variables have been widely employed to capture the nonstationarities of univariate flood series (Strupczewski et al, 2001;Villarini et al, 2009). In this study, the nonstationary marginal distributions of the multivariate flood series…”
Section: Nonstationary Marginal Distributions Based On the Time-varyimentioning
confidence: 99%
See 1 more Smart Citation
“…The time-varying moment model that expresses the distribution parameters or moments as functions of time or some other explanatory variable or variables have been widely employed to capture the nonstationarities of univariate flood series (Strupczewski et al, 2001;Villarini et al, 2009). In this study, the nonstationary marginal distributions of the multivariate flood series…”
Section: Nonstationary Marginal Distributions Based On the Time-varyimentioning
confidence: 99%
“…Due to climate change as well as certain anthropogenic driving forces (Milly et al, 2008), the nonstationarities of both univariate and multivariate flood series have been widely reported (Xiong and Guo, 2004;Villarini et al, 2009;Vogel et al, 2011;López and Francés, 2013;Bender et al, 2014;Xiong et al, 2015;Blöschl et al, 2017;Kundzewicz et al, 2018). The multivariate flood distribution exhibits more complex nonstationarity behaviours than the univariate distribution, including nonstationarities of individual margins and the dependence structure between the margins (Quessy et al, 2013;Bender et al, 2014;Xiong et al, 2015;Kwon et al, 2016;Sarhadi et al, 2016;Qi and Liu, 2017;Vezzoli et al, 2017;Bracken et al, 2018;Salvadori et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…But the optimum time-varying copulas perform better than stationary ones for Z-Q and Z-S in terms of AICc. Frank is found to be the more appropriate bivariate copula for both Z-Q and Z-S, and parameters θ t ZQ , θ t ZS expressed in Equations (12) and (13), respectively, as below: Figure 3b shows the QQ plot of the two bivariate copulas above. It displays a good agreement between empirical distribution and theoretical distribution.…”
Section: Nonstationary Dependence Of Bivariate Flood Variablesmentioning
confidence: 99%
“…Yet, the designs of hydraulic structures (e.g., dam spillways, dikes, and river channels), cross drainage structures (e.g., culverts and bridges) and urban drainage systems require not only peak discharge (Q) value but also peak water stage (Z) and suspended sediment load (S). In fact, the multivariate frequency analysis can provide more comprehensive understanding of the flood event than simple univariate analysis [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, it has been widely applied to various aspects of hydrological studies [13]. The main applications of the Copula Function include the analysis of: precipitation characteristics [12], the correlation between flood peak and flood volume [14,15], the frequency and recurrence interval of floods [16][17][18], characteristics of storms [19,20], the frequency and recurrence intervals of droughts [21], drought assessment [22], risk assessment [23], and an assessment of environmental hydrological model performance [24]. Due to the specialty of the water table, the establishment of the Copula Function for this purpose is relatively difficult; therefore, no research that uses the Copula Function to analyze the water table has been reported.…”
Section: Introductionmentioning
confidence: 99%